The gut microbiota-SCFA-inflammation axis in patients with AECOPD. - Hengjing Zhu; Chen Wu; Haiyan Wu; Juan Liu; Wu Ye; Tian Zhao; Zhijun Li (PLoS ONE)
Objectives The aim of the study was to explore the alteration of microbiota and SCFA in gut and inflammation in acute exacerbation chronic obstructive pulmonary disease (AECOPD) patients, and to test the hypothesis that a disorder of gut microbiota will lead to the alteration of SCFA, which will aggravate inflammation in AECOPD patients. Methods and results 24 patients with AECOPD and 18 healthy volunteers were included in the study. Gut microbiota were analyzed by 16S rDNA and serum was used to detect levels of inflammatory factors by ELISA. Fatty acid concentrations were determined in lumen via gas chromatography-mass spectrometry. The richness and diversity of gut microbiota were decreased in AECOPD patients. β-diversity analysis revealed differences between AECOPD patients and healthy controls. p_Bacteroidetes, g_Paraprevotella, g_Ruminococcus2, g_Parasutterella, o_Rhodospirillales, and g_Romboutsia in the healthy controls and p_Firmicutes, o_Actinomycetales, f_Actinomycetadeae, g_Actinomyces, g_Mogibacterium, f_Veillonellaceae, f_Enterococcaceae, and g_Enterococcus in AECOPD patients were the most abundant microbiota. SCFA levels were decreased in patients with AECOPD. In addition, the results demonstrated that except for a reduction in IL-6, there was no change in inflammatory markers in AECOPD patients. Conclusion In AECOPD patients, the gut microbiota-SCFA-inflammation axis is augmented, with decreased diversity and abundance of gut microbiota, leading to a reduction in SCFA and an imbalance of inflammation.